Bullying the inside story - Leigh, Richard; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2000)
This video is a view inside the mind of Ben, a typical student in secondary school. Ben finds himself in a variety of situations in which he is potentially a victim, bully and on-looker of some unpleasant business in school. As he faces three key scenarios, he debate in his mind the pros and cons of each dilemma
Title from title screen
Executive producer, Stephen Skok ; editor, Richard Leigh ; music, Stuart manderson, David Waterworth ; sound, Tim Mummery ; camera, Joel de Courcy Browne ; script, Richard Leigh
Voice over: Katherine Halliday
Keywords: Bullying in schools; Bullying